Exploratory research to determine student cognitive engagement from heart rate, implementing active learning activities, in a subject of the industrial engineering program at the Escuela Colombiana de Ingeniería Julio Garavito. - Ladino Nocua, Andrea Catalina (Maestría en Ingeniería Industrial, 2021)
The COVID-19 emergency forced educational institutions to adopt measures that would allow them to continue their educative processes in a virtual environment. The various obstacles that students have had to face have affected their engagement and motivation. Identifying factors such as student cognitive engagement in distance learning allows make timely decisions that favor the learning process. In this study, an exploratory investigation was carried out to identify student cognitive engagement in distance lessons, through heart rate, using heart rate bands in university students of the industrial engineering program in Colombia. With the data treatment and the use of a quadrant model, which related a non-self-report method (heart rate) with a self-report method (questionnaire), we obtained the following results: the heart rate has a significant variation during an active learning activity, which can be positive or negative, this indicates that the students experience cognitive engagement; the trend of the heart rate during a lesson depends on internal factors that are directly related to the active learning activities developed, and passive learning activities like the projection of a video can cause an increase in heart rate if students are instructed to do an activity after the video. We expect this study provide input for future research assessing student cognitive engagement using physiological characteristics as a tool.

La emergencia COVID-19 obligó a las instituciones educativas a adoptar medidas que les permitieran que les permitiera continuar con sus procesos educativos en un entorno virtual. Los diversos obstáculos que los estudiantes han tenido que enfrentar han afectado su compromiso y motivación. La identificación de factores como el compromiso cognitivo del estudiante en la educación a distancia permite tomar decisiones oportunas que favorezcan el proceso de aprendizaje. En este estudio se realizó una investigación exploratoria para identificar el compromiso cognitivo del estudiante en las clases a distancia, a través de la frecuencia cardíaca, utilizando en estudiantes universitarios del programa de ingeniería industrial en Colombia. Con los datos tratamiento de datos y el uso de un modelo de cuadrantes, que relacionó un método de no auto-reporte (frecuencia cardiaca) con un método de autoinforme (cuestionario), se obtuvieron los siguientes resultados: la frecuencia cardíaca tiene una variación significativa durante una actividad de aprendizaje activo, que puede ser positiva o negativa, esto Esto indica que los estudiantes experimentan un compromiso cognitivo; la tendencia de la frecuencia cardíaca durante la tendencia de la frecuencia cardíaca durante una clase depende de factores internos que están directamente relacionados con las actividades de aprendizaje activo actividades de aprendizaje activo, y las actividades de aprendizaje pasivo, como la proyección de un vídeo, pueden frecuencia cardíaca si se indica a los alumnos que realicen una actividad después del vídeo. Esperamos que este estudio aporte para futuras investigaciones que evalúen el compromiso cognitivo de los estudiantes utilizando las características fisiológicas fisiológicas como herramienta.
Keywords: Frecuencia cardiaca; COVID 19; Heart rate; Student engagement; Active learning; Non-self-report; COVID 19; Compromiso de los estudiantes; Frecuencia cardiaca; Aprendizaje activo; No autoinforme; COVID 19